2005
DOI: 10.1111/j.1365-2141.2005.05430.x
|View full text |Cite
|
Sign up to set email alerts
|

Teicoplanin‐dependent antibodies: detection and characterization

Abstract: Summary There are only a few reports of thrombocytopenia associated with clinical doses of teicoplanin, a glycopeptide antibiotic used against Gram‐positive bacteria. We investigated 39 patients receiving teicoplanin; 31 were thrombocytopenic with platelet counts between 1–105 × 109/l and 8 were not thrombocytopenic. We identified 14 thrombocytopenic cases (45%) and two (25%) non‐thrombocytopenic cases with IgG teicoplanin‐dependent platelet‐reactive antibodies. Use of glycoprotein (GP) capture enzyme‐linked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…IIb/IIIa (GPIIb/IIIa) available on platelet cells, and rarely caused thrombocytopenia when the antibodies were clinically significant (32). A systemic review and meta-analysis found less frequent teicoplanin-induced nephrotoxicity (elevated serum creatinine level from the baseline value) (RR, 0.44; 95% CI, 0.32 to 0.61), and teicoplanin-induced acute interstitial nephritis leading to irreversible nephrotoxicity was first reported in 1992 (33).…”
Section: Discussionmentioning
confidence: 99%
“…IIb/IIIa (GPIIb/IIIa) available on platelet cells, and rarely caused thrombocytopenia when the antibodies were clinically significant (32). A systemic review and meta-analysis found less frequent teicoplanin-induced nephrotoxicity (elevated serum creatinine level from the baseline value) (RR, 0.44; 95% CI, 0.32 to 0.61), and teicoplanin-induced acute interstitial nephritis leading to irreversible nephrotoxicity was first reported in 1992 (33).…”
Section: Discussionmentioning
confidence: 99%
“…A recent reports indicate that many antibiotic drugs such as teicoplanin and quinine can also cause immune thrombocytopenia. [8][9][10] In this patient, the antibody reacted with the platelets only when vancomycin was administered, not Tazocin. However, in some previously reported cases, there was no evidence of the presence DDPA.…”
Section: Discussionmentioning
confidence: 99%
“…Drug binding to platelet surface can form a new epitope or cause the exposure of a neo-epitope. Glycoprotein Ib-IX and GP IIb/IIIa are most frequently involved in drug binding, which leads to the formation of new epitopes that appear to be very specific for each different drug [6][7][8][9][10][11][12][13][14]. The development of drug-dependent antiplatelet antibodies may thus cause accelerated platelet clearance in vivo and induce severe thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…An immunological mechanism is postulated for many drugs, but so far there is clear evidence of drugdependent antiplatelet antibodies only for a few of them (rifampicin, abciximab, quinine, ranitidine, vancomycin, teicoplanin, sulfonamide, tamoxifene, heparin, and few others) [2,[6][7][8][9][10][11][12][13][14][15][16]. Drug binding to platelet surface can form a new epitope or cause the exposure of a neo-epitope.…”
Section: Discussionmentioning
confidence: 99%